Caught in a communicative catch‐22? Translating the notion of CSR as shared value creation in a Danish CSR frontrunner. (14th August 2017) - Høvring, Christiane Marie
Abstract : There is a growing interest in how the notion of corporate social responsibility (CSR) as shared value creation is translated in Scandinavia. However, current research seems to disregard that the specific institutional context is ambiguous, enabling the organization, and its internal stakeholders to translate the institutional logics into contradictory meanings of CSR as shared value creation. Building on the institutional logics perspective and the metaphor of translation, and framed within a case study of a Danish CSR frontrunner, this paper explores how the notion of CSR as shared value creation is translated at both the organizational and individual level through discourse. The study shows that the organization and its internal stakeholders employ different strategies to reconcile the institutional logics of ethics and economy, suggesting that the translation processes are a complex communicative matter of continuously balancing the contradictory institutional logics to maintain legitimacy in the eyes of external stakeholders.